Isolation and characterization of a cDNA clone specific for avian vitellogenin II. - Protter, A A (1982)
A clone for vitellogenin, a major avian, estrogen responsive egg yolk protein, was isolated from the cDNA library of estrogen-induced rooster liver. Two forms of plasma vitellogenin, vitellogenin I (VTG I) and vitellogenin II (VTG II), distinguishable on the basis of their unique partial proteolysis maps, have been characterized and their corresponding hepatic precursor forms identified. We have used this criterion to specifically characterize which vitellogenin protein had been cloned. Partial proteolysis maps of BTG I and VTG II standards, synthesized in vivo, were compared to maps of protein synthesized in vitro using RNA hybrid-selected by the vitellogenin plasmid. Eight major digest fragments were found common to the in vitro synthesized vitellogenin and the VTG II standard while no fragments were observed to correspond to the VTG I map. A restriction map of the VTG II cDNA clone permits comparison to previously described cDNA and genomic vitellogenin clones.